A dosimetric analysis of proton beam therapy using different snouts. Issue 2 (23rd November 2018) - Iqbal, Khalid; Shamsi, Qurat-ul-ain; Gifford, Kent A; Anum, Sania; Buzdar, Saeed Ahmad
Abstract: Purpose: This exploration is intended to analyse the dosimetric characteristics of proton beams of multiple energies using different snout sizes. Materials and methods: A synchrotron was used for the extraction of eight proton beam energies (100–250 MeV). Dosimetric measurements were taken in a water phantom that was irradiated with a proton beam emanating from the gantry system at angles 0, 90, 180 and 270 degree using a large and a medium snout. The range of beam energies in the phantom, their corresponding centre modulation depth (CMD) and the width of spread out Bragg peak (SOBP) were measured by Markus chamber. Double scattering technique was employed for the creation of SOBPs. Results: The range of proton beams varied from 4·3 cm for 100 MeV beam to 28·5 cm for 250 MeV beam with the medium snout and from 4·3 cm for 100 MeV to 25 cm for 250 MeV beam with large snout in the water phantom. SOBP width showed a variation from 4 to 10 cm with medium and large snout. While determining the output with medium snout, the discrepancy of 1·1% was observed between the maximum and minimum mean values of output for all the given set of energies and angles. There occurred a difference of 0·9% between the maximum and minimum mean values of output with the large snout. Beam output at SOBP centre was 12% higher with large snout as compared to that with medium snout for all the given beam energies. Flatness and symmetry were found within ±2·5% tolerance limits with medium and large snouts. Conclusion: Flatness and symmetry were found within explicit limits with both medium and large snouts. Large snout produced higher beam output than that of medium snout at the centre of SOBP. This exploration can be extended to the determination of beam output, flatness and symmetry with a small snout.